Sporothrix schenckii associated with armadillo hunting in Southern Brazil: epidemiological and antifungal susceptibility profiles Sporothrix schenckii relacionado à caça ao tatu no Sul do Brasil: aspectos epidemiológicos e suscetibilidade dos isolados aos antifúngicos - Sydney Hartz Alves; Cecília Schubert Boettcher; Daniele Carvalho de Oliveira; Giordano Rafael Tronco-Alves; Maria Aparecida Sgaria; Paulo Thadeu; Loiva Therezinha Oliveira; Janio Morais Santurio (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Sporotrichosis is the most common subcutaneous mycosis observed in Brazil and it is generally consequent to a little trauma caused by vegetal particles or spines which inoculate the fungi in the subcutaneous area. Although sporotrichosis had been frequently mentioned with armadillo hunting this form has not been widely reported in Brazil until now. In this study we report ten cases of sporotrichosis evolving the armadillo's hunting diagnosed in some towns located in the central and west regions of Rio Grande do Sul State. METHODS: The cases were established based on clinical and classic mycological laboratorial techniques. The susceptibility tests were conducted by microdilution technique according to M38-A2 CLSI documents. RESULTS: Ten cases of sporotrichosis associated with armadillo hunting detected in the State of Rio Grande do Sul were diagnosed by mycological methods. The susceptibility tests of Sporothrix schenckii isolates to antifungal agents itraconazole, ketoconazole and terbinafine showed that all the isolates were susceptible. CONCLUSIONS: The paper discusses some cultural aspects related to hunting of this wild animal as well as possible causes of this unexpected occurrence in southern Brazil. INTRODUÇÃO: A esporotricose constitui-se na micose subcutânea mais frequentemente observada e, na maioria dos casos, a infecção é decorrente de pequenos traumas envolvendo fragmentos vegetais ou espinhos que inoculam o fungo no tecido subcutâneo. Embora frequentemente relacionada a caça a tatus, esta ocorrência tem sido raramente relatada no Brasil. Neste estudo relatamos dez casos envolvendo esta prática, observados em várias cidades das regiões centro e oeste do Estado do Rio Grande do Sul. MÉTODOS: o diagnóstico clínico foi confirmado pelos métodos clássicos de cultura em ágar Mycobiotic, identificação micromorfológica seguida de reversão a fase leveduriforme em ágar BHI. Os testes de suscetibilidade foram realizados pela técnica de microdiluição em caldo, de acordo com as normas ...